2023
DOI: 10.3390/ijerph20032135
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Winter Parks in Cold Regions on Cognition Recovery and Emotion Improvement of Older Adults: An Empirical Study of Changchun Parks

Abstract: Urban parks are one of the primary settings for older adults to exercise, and their health benefits have been confirmed by a large number of studies. However, with the increased social attention to mental health, there is not enough research on the short-term mental health recovery of older adults in parks. Meanwhile, the health recovery effects of winter parks in special climate areas have not been well explored. This study aimed to explore the effects of winter parks in cold regions on the short-term mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Many studies on nostalgia therapy involved music intervention [91] and odor creation [44], which can provide some evidence for this outcome. The path of the latter has also been confirmed by relevant research [16]. The restorative effects of the environment on individuals were not only determined by natural characteristics but also by the tolerance of local attachment.…”
Section: Discussion On the Decomposition Path Of "Nostalgia" In The E...mentioning
confidence: 65%
See 2 more Smart Citations
“…Many studies on nostalgia therapy involved music intervention [91] and odor creation [44], which can provide some evidence for this outcome. The path of the latter has also been confirmed by relevant research [16]. The restorative effects of the environment on individuals were not only determined by natural characteristics but also by the tolerance of local attachment.…”
Section: Discussion On the Decomposition Path Of "Nostalgia" In The E...mentioning
confidence: 65%
“…(2) Participants were not the first to visit the sample park and had a certain level of familiarity with the park they were visiting. This was because research has shown that familiarity has an impact on emotional perception [16], and there was a survey on local attachment in this study. First-time visitors are usually unable to answer their level of dependence on the environment, and restorative effects may also be mediated by freshness.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating the relationship between landscapes and perceived restorativeness have used psychological questionnaires [36,37]. However, some scholars have employed physiological measurement techniques such as heart rate variability (HRV) [38], blood pressure (BP) [39], skin conductance response (SCR) [3], electroencephalography (EEG) [40], and eye-tracking [41] to more scientifically and objectively verify the relationship between landscapes and perceived restorativeness.…”
Section: Objective and Reliable Measurement Toolsmentioning
confidence: 99%
“…ART suggests that restorative environments contain four key elements: being away, extent, compatibility, and fascination [23]. SRT asserts that nature holds healing potential and that contact with nature reduces stress, thereby facilitating physiological recovery and providing psychological solace [24].…”
Section: Restorative Quality Of Natural Environments and Naturalnessmentioning
confidence: 99%